Study guides

Q: If a equals 2 what is the value of 3a plus 6?

Write your answer...

Submit

Related questions

Yes.

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

10

It is 6a + 4

-2(3a+2)+2=

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2

3a + 2b = (3*6) + (2*5) = 18 + 10 = 283a+2b= (3x6)+(2x5)= 18+10=28

3 times 6 is 18 2 times 5 is 10 18 plus 10 is 28

2 + 3A + 9A = 2 + 12AThe numerical value depends on the value of 'A'.It changes whenever 'A' changes.

6a-3

6 + 12 - 5 = 13

If: -3a+2 = 12 Then: a = -3 and 1/3

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2

2

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

9a^2 + 42at + 49t^2 = (3a + 7t)(3a + 7t)

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

5a

-2

2a2b2+3a2b2-5abc

a2+3a-10 = (a-2)(a+5) when factored